Inovações pedagógicas com o uso de smartphone com base no olhar discente - Guazzelli, Dalva Célia Henriques Rocha (2015)
This research has as its object of study pedagogical innovations with the use of mobile devices, particularly the smartphones. In this direction, has by general objective to analyze the pedagogical innovations using smartphone, based in the eyes of the technical education students. And the specific objectives are: i. analyze whether, in the view of the students, there are, innovative possibilities of learning with mobile devices in pedagogical practices, especially with the smartphone; ii. identify what the students think about the knowledge that students and teachers have about the use of mobile devices as a pedagogical tool; iii. raise whether there are pedagogical experiences lived in the school context of technical education, with the use of mobile devices. Contributions from authors from the field of studies of the technologies and innovations in the education (LÉVY, 2014; GOMEZ, 2004, 2013, 2015; CARLINI & LEITE, 2009; LIBÂNEO, 2012; MERIJE, 2012; CARBONELL, 2002; SANTAELLA, 2013; SACCOL, 2010) and of training and pedagogical practices of teachers (ENGUITA, 1989; FREIRE, 1997, 2000, 2013; GIMENO SACRISTÁN, 1995; NÓVOA, 1995; TARDIF, 2002), compose the theoretical references. Based on the qualitative methodology, the focus group technique (GATTI, 2012) was used to data collect of this study with two students groups of the 1st module of informatics course of a public technical school of the São Paulo’s city. For the treatment of the data was performed content analysis (FRANCO, 2008) of the transcripts of the meeting conducted with each one of the groups and from the questionnaire answers filled individually by students. The results of this study are: i. the verification of the favorable innovative pedagogical possibilities with the use of smartphones, yet with challenges and attention points for the use of these in a pedagogical way, taking into view the discussion of regulation and reliance on mobile technology; ii. the training of the school community about the use of smartphones as innovative pedagogical possibility; iii. the experiences presented by research and by students as favorable to the adoption of possible policies of inclusion of smartphone as a tool to support pedagogical practices. It was concluded, therefore, based on the look of the students that there are possibilities to create pedagogical innovations with the use of smartphones in learning institutions, considering the guidelines that can be built collectively and in a participatory manner by the own educational community in the context of the elaboration process of its Political-Pedagogical Project.